The urban monk : Eastern wisdom and modern hacks to stop time and find success, happiness, and peace - Shojai, Pedram (Rodale, 2016)
"[This work] reveals the secrets to finding an open heart, sharp mind, and grounded sense of well-being, even in the most demanding circumstances"--Front jacket flap.